(untitled) (Faridpur Medical College Journal, 2017)
Acute kidney injury (AKI) occurs in approximately 1-7% of all hospitalized patients. Those patients undergo major surgical procedures are at high risk for AKI due to high volume blood loss, electrolytes disturbance, development of preoperative infection or sepsis and presence of several co-morbidities that may impair renal function. However, published data on postoperative kidney injury are scarce outside the cardiovascular surgery setting. Therefore the study was designed to find out the incidence and risk factors of postoperative acute kidney injury in non-cardiac major surgery. A cross-sectional observational study was conducted in the department of nephrology, BSMMU, Dhaka from January 2014 to December 2014. In this study we found the overall incidence of postoperative AKI 6%. Among the risk factors-male sex, increased age, lengthy operation, exposure to general anesthesia, perioperative hypotension, blood transfusion and use of nephrotoxic drugs (NSAIDs, Aminoglycosides) are important. Faridpur Med. Coll. J. Jul 2016;11(2): 47-49